Arte contemporânea: experiências poéticas - Fernanda Maziero Junqueira (2016)
This dissertation researches mediation in museums and exhibitions of contemporary art. From the supposed distance of the public before contemporary art and using the possibilities of experimentation it offers, concepts were raised related to the aesthetic experience, emancipation of the observer and the opening of the work of art in order to select and propose strategies of sensitization that may benefit the autonomous enjoyment of the viewer. It also covers a reflection on the creation process of the study "Contemporary Art: poetical trials", developed to serve as a stimulus and enrichment tool for the enjoyment of contemporary art, as well as creation, since it is open to the contribution of the reader. Exercises of sensitization contained in the study are based on personal experiences with contemporary art, educational actions already tried and those found in the institutions surveyed. In this study, some contemporary art spaces in Belo Horizonte and the Metropolitan Area are also listed. The survey, as well as the study, are some of the possible ways to understand and address the theme, seeking to contribute to this important discussion and the development of activities in the education area in Contemporary Art Institutions.